Reduced Computed Tomography for Appendicitis in Children after Implementation of Next-day Surgery Clinic Follow-up. Issue 2 (13th March 2023) - Ryan, Sydney; Dudley, Nanette C.; Schunk, Jeff E.; Weng, Cindy; Skarda, David E.; Glissmeyer, Eric W.
Abstract : Introduction: The use of computed tomography (CT) in the emergency department (ED) evaluation of pediatric patients for suspected appendicitis can be safely reduced. However, published examples of reduced CT use also report increased MRI utilization, ED length of stay, hospitalization rates, and in-ED surgical consultation. In addition, previous studies recommended follow-up for undifferentiated abdominal pain, yet none with pediatric surgeons. Therefore, we implemented a diagnostic algorithm that includes an option for next-day surgery clinic follow-up in cases where uncertainty remains after appendix ultrasound (US) to reduce CT utilization without increasing hospital-based resources. Methods: We implemented a diagnostic algorithm in January 2014. We retrospectively identified 4, 577 patients who underwent an evaluation for suspected appendicitis from January 2012 to September 2015. CT utilization was compared before and after implementation using Statistical Process Control. In addition, we evaluated secondary outcomes, including US utilization, hospital admission, surgery clinic follow-up, ED surgery consultation, ED return visits within 7 days, and ED length of stay. Results: Following the implementation of the algorithm, CT utilization decreased significantly from 13.8% to 6%. Forty-eight patients were evaluated the next day in the optional pediatric surgery clinic for 21 months after implementation. There was no significant change in US utilization, hospital admission, ED surgery consultation, ED return visits within 7 days, or ED length of stay. Conclusion: We achieved decreased CT utilization without an increase in the utilization of other hospital-based resources after implementing a pediatric appendicitis evaluation algorithm that includes the option for next-day pediatric surgery clinic follow-up.